The status quo of global geriatric radiation oncology education: A scoping review - Lucinda Morris; Sandra Turner; Jane L. Phillips; Anamika Parmar; Meera Agar (Technical Innovations & Patient Support in Radiation Oncology)
Purpose: To identify potential gaps in geriatric radiation oncology (RO) education worldwide, as measured by geriatric oncology (GO) content within postgraduate RO training program (TP) curricula across 8 focus countries. Methods and materials: The need for improved education around GO is internationally recognized and is a key strategic priority of the International Society of Geriatric Oncology (SIOG).Two reviewers undertook a systematic scoping review from March to September 2023. Focus countries were selected using predefined selection criteria based on national radiation therapy (RT) service provision, RT access and post-graduate specialty training standards. This review is in accordance with evidence-based curriculum design methodology and represents the initial phase i.e., problem identification and needs assessment. Results: Overall RO TP and curriculum elements varied by jurisdiction. Common elements included length of training, summative assessments and prerequisite requirements. Considerable variability exists across TPs around identified learning outcomes, content, TP organization, training networks and accreditation.Across 6 TPs, only 2 had any documented GO curriculum content. Of these, only one contained geriatric RO content scoring moderate to high based on accepted quality benchmarks. Outside official RO TPs, there is considerable GO online education content, including face to face courses, peer-reviewed articles, learning materials and resources relevant to RO postgraduate training worldwide. However accessibility to these learning interventions may be region specific and content is not standardized. Conclusions: As expected, this systematic scoping review has identified significant gaps in GO education within RO TPs worldwide. These findings represent an essential step in the development of evidence-based recommendations for updating standards for GO training within RO training programs and establishing a globally accepted, standardized benchmarks for minimal geriatric RO education. In turn, this will ensure future radiation oncologists are able to deliver a high standard of care to and improve outcomes for older people with cancer.